Revisioning Religion in Ancient Japan - Yoshida, Kazuhiko (Japanese journal of religious studies, 2003)
The study of the history of religion and the history of Buddhism in Japan has recently advanced in great leaps and bounds, with many heretofore unknown facts coming to light. Research on specific topics have gradually accumulated in a variety of fields, and the new perspectives that have emerged have made possible intense debates on how to reevaluate (or "revision") the history of religion and Buddhism in Japan. The field of ancient (kodai) Japanese history-the focus of this essay-has also shown remarkable progress in recent years. Textual studies on the basic historical sources for this period have steadily advanced, including the analysis of the difficult Nihon shoki. In this essay I have tried to absorb the results of recent research and sketch a new history of religion and Buddhism in ancient Japan.